2016
DOI: 10.1016/j.jbusres.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Dress, transformation, and conformity in the heavy rock subculture

Abstract: While the relationship between clothing and the construction of identity has received considerable attention, less attention has been given to identity shifts through acts of consumption. This paper explores the role of dress in a ritual experience during which consumers temporarily shift from one identity mode to another. The qualitative study conducted at two heavy rock music festivals shows that consumers use dress to transform themselves physically which in turn facilitates escape from everyday life. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 61 publications
(90 reference statements)
1
16
0
Order By: Relevance
“…(Arnaud, male, 30s)In a sense, the festival tries to suggest that all social distinction is abolished. Visitors are anonymous, far from their identities in their everyday lives, and they take advantage of this anonymity to completely let go, a behavior observed also at other festivals (Chaney and Goulding, 2016; Kozinets, 2002). Furthermore, beyond music concerts, the festival presents different enhancements to the experience, such as metal sphere motorbike shows.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…(Arnaud, male, 30s)In a sense, the festival tries to suggest that all social distinction is abolished. Visitors are anonymous, far from their identities in their everyday lives, and they take advantage of this anonymity to completely let go, a behavior observed also at other festivals (Chaney and Goulding, 2016; Kozinets, 2002). Furthermore, beyond music concerts, the festival presents different enhancements to the experience, such as metal sphere motorbike shows.…”
Section: Resultsmentioning
confidence: 95%
“…At Hellfest, most of the visitors wear black clothes, gothic makeup, piercings, and other jewelries and eccentric accessories such as studded belts and bracelets to recall the dark and gothic universe of the festival. From this point of view, visitors are indeed the actors of the story created by the festival and they wear the stage costumes (Chaney and Goulding, 2016). Visitors seem to experience a total freedom in the way they behave:Hellfest is definitely the place to be.…”
Section: Resultsmentioning
confidence: 99%
“…I acknowledge that I cannot pretend to know how Elizabeth felt about what she wore, but I was hoping to use the boots as a way of stepping out of my everyday identity, in the way that clothing can help us shift our self from one mode of being to another. 77 I was trying what Vanessa Agnew describes as "substitution-the reenactor for the historical agent [and] the present for the past," and through this to perhaps experience some of the haunting that had eluded me. 78 I also hired a local drone photographer to gain a different view of the same properties; to try to see further, to see more.…”
Section: Easter 2017: Visit Onementioning
confidence: 99%
“…One of the key dimensions of extraordinary experiences is the idea of intense socializing or communing (Holt, 1995). This implies the nurturing and flourishing of positive and collaborative social interactions between participants, leading to communal integration (Arnould & Price, 1993;Chaney & Goulding, 2016;Schouten et al, 2007). However, prior research has also shown that limited social interactions might emerge within the sphere of extraordinary experiences and require constant negotiation by participants (Husemann et al, 2016;Tumbat & Belk, 2011 The tension between individualism and tribalism, one of the hallmarks of postmodern consumer culture (Firat & Venkatesh, 1995;Tumbat & Belk, 2011) Dennis reveals the tension between the functional ('instrumental') dimensions of consumption experiences, and the romantic ones predominantly identified in prior theorizations of extraordinary experiences and associated with the creation of communitas (Arnould & Price, 1993;Turner, 1969).…”
Section: Immersion/communingmentioning
confidence: 99%